Bilateral Congenital Pseudarthrosis of the Tibia with Neurofibromatosis Type 1: Case Report and Literature Review - Bunyamin Ari; Sabit Numan Kuyubasi (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021